(untitled) (Fiep Bulletin - online, 2025)
Instagram influences the search for the ideal body and exercise, but it can also cause pressure on body image. The objective of this work was to understand the role of the social network Instagram in the practice of physical exercise, body image and its implications. This is a bibliographic review study of a basic and integrative nature, which aims to discuss the topic under study in a descriptive way and obtain conclusions from a qualitative approach, where articles were selected for analysis. The results demonstrated that Instagram influences the practice of physical activity in several ways. Exposure to healthy bodies and fitness influences physical activity, but inaccurate information can lead to inappropriate practices. Additionally, Instagram’s social interaction motivates, but comparisons and aesthetic pressures can cause body dissatisfaction, especially in women. Therefore, the influence of Instagram on physical activity can be positive or negative.